Tingkat Ketergantungan Nikotin Perokok Vape Berdasarkan Uji Fagerstrom pada Mahasiswa Universitas Garut - Intan Arie Yulian; Mohammad Rizki Akbar; Alya Tursina (Bandung Conference Series: Medical Science, 2022)
Abstract. The use of vape cigarettes can cause serious health problems that are sometimes deadly. Initially, vape cigarettes were intended as a substitute for conventional cigarettes, but vape cigarettes also still contain harmful chemicals, one of which is nicotine, which is a substance that causes addiction (addiction). There are various ways to assess a person's level of dependence on nicotine, the most commonly used is the Fagerstrom test. The purpose of the study was to determine the level of nicotine dependence of vape smokers based on the Fagerstrom test on Garut University students. Descriptive research method with a cross-sectional design. The sampling technique was purposive sampling, the number of samples was 51 people. The research instrument was a questionnaire on respondents' demographic data and the PDPI version of the Fagerstrom Test for Nicotine Dependence (FTND) questionnaire. The results showed that the level of nicotine dependence of vape smokers was mostly in the moderate criteria as many as 31 people (60.8%) with an average value of the nicotine dependence level of vape smokers (7.67). It was concluded that the level of nicotine dependence as measured by the Fagerstrom test in vape cigarette users was in the moderate category. Vape users have the potential to become addicted because the high-voltage tube in the vape can drain large amounts of nicotine into the body. Abstrak. Penggunaan rokok rokok vape bisa menimbulkan permasalah kesehatan serius yang terkadang mematikan. Pada awalnya rokok vape ditujukan sebagai pengganti rokok konvensional, namun rokok vape juga masih mengandung zat kimia berbahaya, salah satunya nikotin yang merupakan zat penyebab kecanduan (adiksi). Terdapat berbagai cara untuk menilai tingkat ketergantungan seseorang terhadap nikotin, paling umum digunakan adalah dengan uji Fagerstrom. Tujuan penelitian untuk mengetahui tingkat ketergantungan nikotin perokok vape berdasarkan uji Fagerstrom pada mahasiswa Universitas Garut. Metode penelitian deskriptif dengan desain potong lintang. Teknik sampling dengan cara Purposive sampling, jumlah sampel sebanyak 51 orang. Instrumen penelitian berupa kuesioner data demografi responden serta kuesioner Fagerstrom Test for Nicotine Dependence (FTND) versi PDPI. Hasil penelitian, tingkat ketergantungan nikotin perokok vape sebagian besar berada pada kriteria sedang sebanyak 31 orang (60,8%) dengan nilai rata-rata tingkat ketergantungan nikotin perokok vape (7,67). Disimpulkan bahwa tingkat ketergantungan nikotin yang diukur dengan Uji Fagerstrom pada pengguna rokok vape berada pada kategori sedang. Pengguna vape berpotensi terhadap ketergantungan karena tabung dengan tegangan tinggi pada vape dapat mengalirkan nikotin dalam jumlah besar ke dalam tubuh.